2012
DOI: 10.5194/isprsarchives-xxxix-b5-393-2012
|View full text |Cite
|
Sign up to set email alerts
|

Automated Low-Cost Photogrammetry for Flexible Structure Monitoring

Abstract: ABSTRACT:Structural monitoring requires instruments which can provide high precision and accuracy, reliable measurements at good temporal resolution and rapid processing speeds. Long-term campaigns and flexible structures are regarded as two of the most challenging subjects in monitoring engineering structures. Long-term monitoring in civil engineering is generally considered to be labourintensive and financially expensive and it can take significant effort to arrange the necessary human resources, transportat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Photogrammetric techniques are used to evaluate the structural integrity and characteristics of flexible structures; however, they are often used for evaluative purposes on large structures such as structural beams, underground piping systems and geographical mapping of large areas. [26][27][28] Other structural techniques were considered since there is a body of work looking at approaches other than optical ones [29]; however, these techniques applied to curing concrete offer little benefit in the practical application of a method to evaluate a fast moving membrane sheath such as the waterless trap under a negative pressure. The techniques applied to this research have been developed specifically for this purpose, based on previous work to develop boundary equations for building drainage applications although the techniques were not fully developed in that research [30].…”
Section: Modelling Waterless Trapsmentioning
confidence: 99%
“…Photogrammetric techniques are used to evaluate the structural integrity and characteristics of flexible structures; however, they are often used for evaluative purposes on large structures such as structural beams, underground piping systems and geographical mapping of large areas. [26][27][28] Other structural techniques were considered since there is a body of work looking at approaches other than optical ones [29]; however, these techniques applied to curing concrete offer little benefit in the practical application of a method to evaluate a fast moving membrane sheath such as the waterless trap under a negative pressure. The techniques applied to this research have been developed specifically for this purpose, based on previous work to develop boundary equations for building drainage applications although the techniques were not fully developed in that research [30].…”
Section: Modelling Waterless Trapsmentioning
confidence: 99%
“…The results showed that properly calibrated smartphone cameras can be used for photogrammetric tasks with a required accuracy of 1:10,000. The smartphone SfM photogrammetric method has been tested in many fields including flexible structural monitoring [ 18 ], coastal monitoring [ 19 , 20 , 21 ], auxiliary medical examinations [ 22 , 23 ], alpine alluvial fan surveys [ 24 ], and soil water erosion [ 25 ]. Although the smartphone SfM photogrammetric method has been successfully used in these applications and has produced high-resolution results, to the best of the authors’ knowledge, this approach has rarely been used for mapping the topography of rock joint surfaces in geotechnical laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Although their quality is still a limitation for obtaining of highly accurate images, they have the great advantage of being totally portable and are almost always to hand. Currently, they offer a low‐cost option for close‐range photogrammetric applications, including the creation of three‐dimensional (3D) models for a wide range of purposes, including structural monitoring (Wang et al., ), geomorphology (Micheletti et al., ), creative industries (Nocerino et al., ) and medical applications (Abreu de Souza et al., ; Hellwich et al., ; Hernandez & Lemaire, ), among others. Other low‐cost non‐metric cameras, such as webcams, have also been used for close‐range modelling (Chong and Brownstein, ).…”
Section: Introductionmentioning
confidence: 99%